Prevalence, Molecular Characterization, and Antibiotic Susceptibility of Vibrio parahaemolyticus from Ready-to-Eat Foods in China - Xie, Tengfei; Xu, Xiaoke; Wu, Qingping; Zhang, Jumei; Cheng, Jianheng (Frontiers in Microbiology, 2016)
Vibrio parahaemolyticus is the leading cause of foodborne outbreaks, particularly outbreaks associated with consumption of fish and shellfish, and represents a major threat to human health worldwide. This bacterium habors two main virulence factors: the thermostable direct hemolysin (tdh) and TDH-related hemolysin (trh) Additionally, various serotypes have been identified. The extensive use of antibiotics is a contributing factor in the increasing incidence of antimicrobial resistant V.parahaemolyticus. In the current study, we aimed to determine the incidence and features of V. parahaemolyticus in ready-to-eat (RTE) foods in China. We found 39 V. parahaemolyticus strains on Chinese RTE foods through investigate 511 RTE foods samples in 24 cities in China. All isolates were analyzed for the presence of tdh and trh by PCR, serotyping was performed using multiplex PCR , antibiotic susceptibility analysis was carried out using the disk diffusion method, and molecular typing by enterobacterial repetitive intergenic consensus sequence PCR (ERIC-PCR) typing and multi-locus sequence typing (MLST). The results showed that none of the isolates were positive for tdh and trh.Most of the isolates were type O2. Antimicrobial susceptibility results indicated that most strains were resistant to streptomycin, cefazolin and ampicillin. The isolates were grouped into five clusters by ERIC-PCR and four clusters by MLST. We updated 10 novel loci and 33 sequence types (STs) in MLST database. Thus, our finds demonstrated the presence of V. parahaemolyticus in Chinese RTE foods, provided insights into the the dissemination of antibiotic resistant strains, and improved our knowledge of methods of microbiological risk assessment in RTE foods.